Competencies and Development Needs of Physician Managers in Nigeria: A Case Study of selected hospitals in Ibadan City, Oyo State - Daramola , Gbemisola A.; Awolusi, Olawumi Dele (Journal of Social and Development Sciences, 2021)
The physician is traditionally the head of the medical team. To be an effective and efficient team leader is not innate but requires acquiring some competencies. The medical school curriculum was deficient in this regard hence the need for acquisition of these skills through training. Consequently, the present study aims to assess the influence of leadership competencies and Development Needs on the job performance of Physician Mangers. A cross-sectional survey was distributed among Physician Managers in various hospital types that were purposefully selected. Ten Physician Managers were also interviewed for in-depth information of skills they require to perform well. Descriptive and inferential statistics were used to summarize the items of the questionnaire at 5% level of significance and to determine if a significant difference existed between groups of Physician managers. Results show that possessing the competencies; communication and relationship management, leadership and business skills and knowledge do influence the job performance of Physician Mangers. There was a significant difference between physicians that had formal training in management and those that had none in the communication and professionalism domains. Seven Physician Managers from different types of hospitals were interviewed, two of them females. They had been in managerial positions from 6months to 34 years. They all emphasised communication and leadership skills as important competencies for every physician manager. They all also suggested that management training must be introduced either during undergraduate or postgraduate training and that physician as head of the medical team require regular management update training.